Neolithic Burial Rituals in Anatolia and the Method of Separating Skulls - Sara Saeed Abdul Redha / Fadel Kazem Hanoun ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Anatolia was distinguished, in Neolithic, by adopting several methods of burial, including the method of separating the skull from the skeleton of the dead, with removing the meat from the dead body, and taking care of this skull, by decorating it, including the belief in respecting ancestors, some researchers called for a theory, which they called ancestor worship. In the researcher’s point of view, the belief did not reach the stage of religiosity, rather, it is a kind of veneration and reverence for some dead relatives, perhaps. This was not limited to the elderly, but rather skulls of children, women, young men, and juveniles were found. In addition, this method was not invented in Anatolia, but was influenced by the culture of the settlements. neolithic Anatolia, from settlements in the northern levant.